2002
DOI: 10.1046/j.1365-8711.2002.05988.x
|View full text |Cite
|
Sign up to set email alerts
|

The O IV and S IV intercombination lines in the ultraviolet spectra of astrophysical sources

Abstract: New electron density diagnostic line ratios are presented for the O iv 2s22p 2P–2s2p24P and S iv 3s23p 2P–3s3p24P intercombination lines around 1400Å. A comparison of these with observational data for the symbiotic star RR Telescopii (RR Tel), obtained with the Space Telescope Imaging Spectrograph (STIS), reveals generally very good agreement between theory and observation. However the S iv2P3/2–4P1/2 transition at 1423.824Å is found to be blended with an unknown feature at 1423.774 Å. The linewidth for the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 33 publications
9
47
0
Order By: Relevance
“…To the best of our knowledge, this is the first time we can directly diagnose such high electron number densities in the TR plasma during a flare. Density diagnostics based on the use of S iv line ratios with previous instruments in the past were complicated by the presence of line blends which could not be properly resolved and problems in the atomic data (Dufton et al 1982a;Cook et al 1995), as also pointed out by Keenan et al (2002b). In this work we have shown that the S iv 1404.85 Å line can be accurately de-blended from the O iv 1404.85 Å line in the high density interval above 10 12 cm −3 .…”
Section: Discussion and Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first time we can directly diagnose such high electron number densities in the TR plasma during a flare. Density diagnostics based on the use of S iv line ratios with previous instruments in the past were complicated by the presence of line blends which could not be properly resolved and problems in the atomic data (Dufton et al 1982a;Cook et al 1995), as also pointed out by Keenan et al (2002b). In this work we have shown that the S iv 1404.85 Å line can be accurately de-blended from the O iv 1404.85 Å line in the high density interval above 10 12 cm −3 .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…4.3. We note that previous studies (e.g., Keenan et al 2002a) mainly focused on comparing density diagnostics using the O iv and S iv ratios individually but did not report any comparison on the relative intensity of spectral lines from the two ions.…”
Section: Density Diagnostics In the Ar Noaa 12356mentioning
confidence: 92%
See 3 more Smart Citations